Faktor-Faktor Bauran Pemasaran yang Memengaruhi Keputusan Pembelian di Bukalapak - Yohandira Yohandira; Idqan Fahmi; Alla Asmara (IPB University, 2021)
The growth rate of e-commerce in Indonesia is high. The condition could be seen on the competition map between marketplaces in Indonesia. Bukalapak was one of the top three marketplaces in Indonesia that has seen the most significant decrease in visitor numbers in 2019, at 26 percent precisely. Organizations should formulate marketing strategies in accordance with marketing mix determined based on market analysis to survive in the competitive field. This research aims to analyze consumer perceptions of marketing mix and purchase decision on Bukalapak, analyze marketing mix factors that influence purchase decision on Bukalapak, and formulate marketing strategies to hold back the decline in Bukalapak visitor numbers. The research data were analyzed using Structural Equation Modeling and presented descriptively. The results showed that 66 percent of consumers rated products on Bukalapak had excellent features, 72 percent of consumers rated prices on Bukalapak were reasonable, 64 percent of consumers rated payment methods on Bukalapak were in variety, and shipping discount on Bukalapak was attractive. The marketing mix factors that significantly influenced purchase decision on Bukalapak were place and price. Recommended marketing strategies to hold back the decline in Bukalapak visitors were increasing price variations and optimizing mobile application speeds.